Perancangan Access Open Journal System (AOJS) dengan menggunakan Framework Codeigniter dan ReactJs - Wali, Muhammad; Ahmad, Lukman (KITA Institut, 2018)
a b s t r a c t Open Journal Systems (OJS) is a web-based content management system specifically designed to handle the entire process of scientific publication management. The Ministry of Research, Technology and Higher Education also develops its own index, namely SINTA (Science and Technology Index) which is expected to not only refer to the journal index Scopus. The relationship between Access Indexing and OJS is inseparable where the OJS is a facility in managing journal publications and Access Indexing is a feature to disseminate journal articles to journal searches. This study tries to build an Access Open Journal Systems (AOJS) model that can be used as a form of publication and publishing management on international indexing. The application allows updating of data/content and sharing from various online journal sources. Access Open Journal Systems (AOJS) can enable end-user users, and still refer to international publishing management standards. It is expected that Access Open Journal Systems (AOJS) can increase publication and management of publishing electronically and be fully implemented by authors, publishers, and partners of reviewers. The Access Open Journal Systems (AOJS) application will take the Open Knowledge Systems (OJS) Public Knowledge Project (PKP) model, with the reason that the Open Journal Systems (OJS) is one of the most widely used OJS and is a recommendation from the Ministry of Research and Technology with PDII LIPI in obtaining National Journal Accreditation (ARJUNA) and facilitates researchers to see, adapt, and modify for the purposes of this study. Broadly speaking this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. Specifically, the output to be achieved Prototype as technology engineering: This research will produce a prototype Open source Access Open Journal Systems (AOJS) software, which can be used by journal publishing managers and to support content publication. The results of this study are an open source software called Open source Access Open Journal Systems (AOJS) and developed with framework CodeIgniter and React-Js. a b s t r a k Open Journal Systems (OJS) merupakan sebuah sistem manajemen konten berbasis web yang khusus dibuat untuk menangani keseluruhan proses manajemen publikasi ilmiah. Kemenristekdikti juga mengembangkan indeks sendiri yaitu SINTA (Science and Technology Index) yang diharapkan index jurnal tidak hanya mengacu pada Scopus. Hubungan Access Indexing dengan OJS menjadi hal yang tidak terpisahkan dimana OJS menjadi fasilitas dalam mengelola terbitan jurnal dan Acces Indexing menjadi fitur untuk menyebarluaskan artikel jurnal pada pencarian jurnal. Penelitian ini mencoba untuk membangun model Acces Open Journal Systems (AOJS) yang dapat digunakan sebagai bentuk manajemen publikasi dan penerbitan pada indexing internasional. Aplikasi tersebut memungkinkan pembaharuan data/konten dan sharing dari berbagai sumber jurnal online. Acces Open Journal Systems (AOJS) dapat memungkinkan pengguna end user, serta tetap mengacu pada standar manajemen pengelola terbitan internasional. Diharapkan dengan adanya Acces Open Journal Systems (AOJS) dapat meningkatkan publikasi dan manajemen penerbitan secara elektronik serta sepenuhnya dilaksanakan baik oleh penulis, penerbit maupun mitra bestari (reviewer). Aplikasi Acces Open Journal Systems (AOJS) akan mengambil model Open Journal Systems (OJS) Public Knowledge Project (PKP), dengan alasan Open Journal Systems (OJS) tersebut adalah salah satu OJS yang paling banyak digunakan dan merupakan rekomendasi dari Kementerian Riset dan Teknologi dengan PDII LIPI dalam mendapatkan Akreditasi Jurnal Nasional (ARJUNA) serta memudahkan peneliti untuk melihat, mengadaptasi, dan memodifikasi untuk keperluan penelitian ini. Secara garis besar penelitian ini dibagi dalam tiga tahapan, yaitu pengumpulan data pra pengembangan, pengembangan serta implementasi, dan pengumpulan data pasca pengembangan. Secara spesifik luaran yang akan dicapai Purwarupa sebagai rekayasa teknologi: Penelitian ini akan menghasilkan sebuah purwarupa perangkat lunak Open source Acces Open Journal Systems (AOJS), yang dapat digunakan oleh pengelola terbitan jurnal serta untuk menunjang publikasi konten. Hasil dari penelitian ini sebuah perangkat lunak berbasis open source yang diberi nama Open source Acces Open Journal Systems (AOJS) dan dikembangkan dengan framework codelnigter dan React-Js.